Enhancing Early Reading Competencies in Students with Mild Intellectual Disabilities: A Montessori Method Intervention Study - Yuliana, Yuliana; Pujaningsih, Pujaningsih (Papanda Publisher, 2025)
Students with mild intellectual disabilities frequently encounter significant challenges in acquiring early reading skills, yet limited empirical evidence exists regarding effective instructional approaches tailored to their learning needs. This classroom action research investigated the effectiveness of the Montessori method in improving early reading competencies among slow learners in first-grade elementary education. Conducted over four weeks at SD Negeri 001 Muara Wahau, Indonesia, the study employed a Kemmis and McTaggart cyclical model comprising two intervention cycles. The participant was a first-grade male student identified as a slow learner demonstrating difficulties in letter recognition, phonetic sound production, and word reading. The intervention incorporated Montessori principles including concrete manipulatives (picture-word cards, letter cards, sandpaper letters), multisensory engagement activities, and systematic phonics instruction. Data collection utilized reading performance tests, structured observational checklists, and progress monitoring protocols. Results demonstrated substantial improvement from 20% baseline accuracy to 95% mastery level, representing a 75-percentage-point gain that exceeded the predetermined 80% success criterion. Letter recognition and phonetic sound production achieved 100% accuracy by Cycle II, while both consonant-vowel repetitive patterns and consonant-vowel-consonant-vowel patterns showed marked improvement. These findings provide empirical evidence that the Montessori method effectively enhances early reading competencies in students with mild intellectual disabilities, challenging deficit-oriented perspectives and validating multisensory structured literacy approaches for inclusive educational settings.